2017
DOI: 10.1016/j.nmni.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tigecycline- and vancomycin-resistant Staphylococcus aureus strains among patients with urinary tract infection in Iran

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the major causes of hospital- and community-acquired infections worldwide. Although S. aureus rarely accounts for urinary tract infections (UTI), untreated UTI can lead to several complications. For decades vancomycin has been used for the treatment of MRSA infections. This study was performed to assess the in vitro activity of vancomycin, tigecycline, linezolid and quinupristin/dalfopristin against MRSA isolates from UTI patients. Thirty MRSA strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The overall proportion of MRSA among study participants was 43.4% [95% CI (35.0, 47.0)] which was slightly higher than the study conducted in India. 30 However, this finding was lower than that of the study reported from Debre Markos University, Ethiopia 28 and from other country studies like; Nepal with a prevalence of 82.0%, 31 Iran with a prevalence of 55.6%, 32 and 64.3% reported from Nigeria. 33 This difference in isolation rate of MRSA could be due to the isolation technique (multiple screens) and there might be specific risk factors which are not assessed by this study that might decrease the proportion of MRSA among S. aureus in the current study, sample collection method (they used more than one clinical specimen), variation in study participants (since they collected from patients with a confirmed UTI whereas this study is from UTI suspected participants only).…”
Section: Discussionmentioning
confidence: 53%
“…The overall proportion of MRSA among study participants was 43.4% [95% CI (35.0, 47.0)] which was slightly higher than the study conducted in India. 30 However, this finding was lower than that of the study reported from Debre Markos University, Ethiopia 28 and from other country studies like; Nepal with a prevalence of 82.0%, 31 Iran with a prevalence of 55.6%, 32 and 64.3% reported from Nigeria. 33 This difference in isolation rate of MRSA could be due to the isolation technique (multiple screens) and there might be specific risk factors which are not assessed by this study that might decrease the proportion of MRSA among S. aureus in the current study, sample collection method (they used more than one clinical specimen), variation in study participants (since they collected from patients with a confirmed UTI whereas this study is from UTI suspected participants only).…”
Section: Discussionmentioning
confidence: 53%
“…Similarly, a previous study conducted by Zorgani et al in Libya indicated resistance to tigecycline in 3.6% of their S. aureus isolates tested [24]. In an experiment performed by Yousefi et al on 54 S. aureus isolated from urinary tract infections, 6.6% isolates were found to be resistant to tigecycline [25]. These observations were also supported by findings from Canada, USA, Honduras, El Salvador, France, Germany, Italy, Poland, Nigeria, China, and Taiwan [21].…”
Section: Discussionmentioning
confidence: 73%
“…However, different resistance rates to tigecycline among S. aureus isolates are reported in Libya (3.6%), 25 Turkey (2%), 26 and Iran (6.6%). 9 Recently published data from Asian countries indicated a low prevalence of resistance to fusidic acid (<10%). 27,28 We found a low prevalence (4.7%) of resistance to fusidic acid among our isolates carrying fusB (3 isolates), and fusC (1 isolate) genes.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Due to emerging simultaneous resistance to several antibacterial agents, the choice of chemotherapeutic options and treatment of serious infections caused by S. aureus has become problematic. [7][8][9] Although various antibiotics such as vancomycin, linezolid, and quinupristin-dalfopristin may be considered as drugs of choice, S. aureus strains with reduced susceptibility and resistance to these agents also emerged. Therefore, the use of macrolide-lincosamide-streptogramin B (MLSB) antibiotics as an alternative approach to treating such infections was taken into consideration.…”
Section: Introductionmentioning
confidence: 99%